THE USE OF ADAPTIVE LEARNING SYSTEMS TO IMPROVE STUDENTS PROBLEM SOLVING ABILITY IN MATHEMATICS - ika sartika (Jurnal Penelitian Samudra, 2026)
Problem-solving ability is a core competence in mathematics learning and a key indicator of students’ higher-order thinking skills. However, many students experience difficulties in solving mathematical problems due to differences in prior knowledge, learning pace, and cognitive abilities. Adaptive Learning Systems (ALS) have emerged as an innovative instructional approach that personalizes learning experiences based on individual student needs. This study aims to examine the effectiveness of Adaptive Learning Systems in improving students’ problem-solving ability in mathematics. The research employed a quasi-experimental design with a pretest–posttest control group. The sample consisted of secondary school students divided into an experimental group using an Adaptive Learning System and a control group receiving conventional instruction. Data were collected through problem-solving tests and analyzed using descriptive and inferential statistics. The results indicate that students who learned through the Adaptive Learning System demonstrated significantly higher improvements in mathematical problem-solving ability compared to those in the conventional learning group. These findings suggest that Adaptive Learning Systems can serve as an effective instructional strategy to enhance students’ problem-solving skills in mathematics.